Fruit, Fiber, and Fire : A History of Modern Agriculture in New Mexico - Carleton, William R. (Book collections on Project MUSE., 2021)
Fruit, Fiber, and Fire explores the industrialization of apples, cotton, and chile to illustrate how agriculture has spurred migrations of plants and people and in turn shaped the culture of twentieth-century New Mexico.